The German Environmental Tax Reform: a difference-in-differences analysis of its impacts in European comparison - Daniel Kühnhenrich (Environmental Economics and Policy Studies, 2023)
In 1998, the red-green Schröder government implemented the Environmental Tax Reform (ETR), raising taxes on petrol, diesel, natural gas and heating oil and introducing a new duty on electricity in Germany. At the same time, it cut non-wage labour costs by reducing public pension contributions. The goal was to achieve Germany's Kyoto Protocol emissions targets and to reduce a level of unemployment unprecedented since World War II while avoiding the burden on the public budget through revenue recycling. Employing microdata from household budget surveys of 1998 and 2003, this article analyses whether increased duties on motor fuels and electricity lead to a substantial reduction in households' consumption of these goods. Considering the ETR as a natural experiment, it uses the difference-in-differences approach in a European context with Germany as the treatment group and Italy, Spain and the UK as the control group. Ordinary least square regressions reveal that motor fuel demand is price inelastic, while electricity consumption increased despite the substantial rise in prices. Quartile regressions show that the effect of the motor fuel tax is slightly higher at the bottom than at the upper tail of the distribution supporting the notion that low-level consumers are more likely to find alternative substitutes.
Keywords: 330; Energy taxes; Environmental tax reform; Microdata; Household budget surveys; Difference-in-differences; Regression analysis